Three-dimensional spherical model based XML communication protocols security evaluation method - Hong-yu YANG; Jin-bo YU; Li-xia XIE (Tongxin xuebao)
Aiming at the problems of security assessment in XML communication protocols, a novel three-dimensional spherical model based protocol security evaluation method was proposed. Firstly, a three-dimensional security evaluation index system was constructed through positions of indexes on the spherical shell. Secondly, by using the coordinate's projection area as a measure criterion, evaluation indexes' weights of the first level and the second level were obtained with the analytic hierarchy process (AHP), the sphere and the sector angle. Thirdly, security components values of XML communication protocol were calculated in the aspects of XML's content, communication load and security vulne-rability. Finally, the security evaluation result of XML communication protocol was achieved through quantization calcu-lation and further comprehensive analysis. Experimental results show that this method is competent for the protocol secu-rity evaluation and meets security evaluating requirem L communication protocols effectively.